ITALIA NORWIDA JAKO CAŁOŚĆ (Z PROBLEMÓW ESTETYKI TEOLOGICZNEJ) - Kuczera-Chachulska, Bernadetta (Colloquia Litteraria, 2019)
Norwid’s Italy as a Whole. Problems in Theological Aesthetics The article analyzes several of Norwid’s most celebrated poems (w weronie, Fortepian Szopena, among others) and points to a significant proximity of the poet’s notion of art and Hans Urs von Balthasar’s theological-aesthetic thought. The common space of reflection of these two thinkers denotes an understanding of art as a means and medium for the expression of the biblical Revelation. The article further explores such perception of the ex- pression of theological truths (in von Balthasar’s terminology: theological aesthetics), especially as it becomes prominent in Norwid’s work engaging in the ‘Italian’ themes.